1991
DOI: 10.1111/j.1751-1097.1991.tb02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Translational Mobility in the Adsorbed State. Bimolecular Deactivation Kinetics of Laser‐excited Azaaromatics on Microporous Silica*

Abstract: A series of polycondensed aromatic N‐heterocycles (acridine, benzo‐f‐quinoline 1,2,7,8‐dibenzacridine and 3,4,5,6‐dibenzacridine) were adsorbed from the gas phase and from liquid solution on highly dispersed silica gels with very different specific surface areas and pore sizes. The translational mobility of the adsorbed species was quantified by the triplet decay and the delayed fluorescence following bimolecular triplet‐triplet annihilation after pulsed laser irradiation. The decay kinetics were analyzed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…, respectively, where R and R´are diffuse reflectance from the surface of the samples with and without TPP, respectively, and R t is the reflectance observed at time t after the laser pulse [1][2][3]. The validity of Kubelka-Munk treatment for analysis of transient decays in the present system was confirmed earlier [5][6][7][8][9].…”
Section: Instrumentation and Data Analysis The De-supporting
confidence: 77%
See 1 more Smart Citation
“…, respectively, where R and R´are diffuse reflectance from the surface of the samples with and without TPP, respectively, and R t is the reflectance observed at time t after the laser pulse [1][2][3]. The validity of Kubelka-Munk treatment for analysis of transient decays in the present system was confirmed earlier [5][6][7][8][9].…”
Section: Instrumentation and Data Analysis The De-supporting
confidence: 77%
“…This process needs considerable amounts of T and may be achieved with strong laser pulse as an excitation source. The study of TTA kinetics at gas/solid and gas/liquid interfaces was carried out in order to probe the effect of surface topology, molecular diffusion, environment and organization [1][2][3][4][5]. The TTA requires molecular mobility of T which may be restricted by the adsorption and by the reaction space geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Transient signal intensities were near saturation under experimental conditions and demonstrated almost total conversion of ground state into transient, implying the validity of Kubelka-Munk treatment for analysis of transient decays. [4][5][6] Results Solid-State 1 H NMR of n-Decanol Films on the NaA External Surface. Lines in 1 H solid-state NMR spectra are, in general, very broad and this is explained by the very strong homonuclear dipole-dipole interaction which scales with (HH distance) -3 , and consequently, wide-line static 1 H spectra are sensitive to molecular motion.…”
Section: Methodsmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry and Owner Societies 2011 showed that the diffusion coefficients of tetracene on silica with 150 A ˚pores remained approximately constant when the pretreatment temperature was increased from 25 to 600 • C, but that the mobile fraction increases with increasing temperature. However, Oelkrug et al 21 reported a reduction in the mobility of aromatic nitrogen heterocycles on silica gel having 60 A ˚pores with increasing pre-treatment temperature of the surface. Table 2 summarises the results obtained and it can be seen that to within experimental error there is little or no dependence of activation energy (E a ) on the pre-treatment temperature (PTT) or the identity of the sensitiser.…”
Section: Activation Energies In Bimolecular Systemsmentioning
confidence: 99%
“…17 However, the study of the kinetics of decay or reactions of "dark" states such as triplets and radical ions has been through the use of diffuse reflectance spectroscopy. 1-3,5-8,12, [16][17][18]21,23,26 This latter technique has been used by ourselves to study the long time decay (greater than 30 s) of anthracene radical cations. 1 This technique works well as most anthracene derivatives have a distinctive radical cation absorption peak in the 700-800 nm region.…”
Section: Introductionmentioning
confidence: 99%